Periungual desquamation in a Japanese Adult recovering from severe COVID-19 (2020)
We report a case of 50-year-old Japanese male who developed periungual desquamation in hand and feet, during recovery phase of severe COVID-19. As coronary lesions (CALs) have been reported during the recovery phase of severe COVID-19 in children as well as Kawasaki disease, caution may be necessary in adults as well.